Evapotranspiração máxima da cana de açúcar estimada pelo algoritimo SAFER - Mussi, Rodolfo Fernandes (2017)
Sugarcane is the main irrigated crop in Brazil (more than 25% of all irrigated areas in the country), requiring cumulative rainfall during its 1,000 mm year-1 cycle. Thus, evapotranspiration is a fundamental information for planning, hydro-hydraulic design, water management along the cycle and management of water resources for culture. Irrigation planning based on empirical values of the crop coefficient (Kc) can increase production costs, reduce product quality and yield. The use of remote sensing associated with orbital images and algorithms, aid in the estimation of evapotranspiration when combined with physical models. The SAFER is a simplified algorithm when compared to the others that are also used to determine the current evapotranspiration of the crop, since it is based on the Penman-Monteith equation to obtain the evapotranspiration, being this factor the main one to choose this algorithm for its use . In this way, the objective of this study was to determine the evapotranspiration of the sugarcane crop (first cycle), as well as the respective crop coefficients (Kc) for the region of the São Patrício Valley in Goiás, by energy balance (Using the remote sensing allied to the SAFER algorithm) and water balance (monitoring the atmosphere and water in the soil). Thus, this study had the objective of estimating crop evapotranspiration (ETa) of the variety IAC 91-1099 of sugarcane by the SAFER (Simple Algorithm for Evapotranspiration Retrieving) energy balance model using images from Landsat 8 OLI / TIRS, and comparison with soil water balance method (ETBHS) using soil moisture sensors (EC-5) and reference evapotranspiration (ETo Penman-Monteith). The study was carried out at Esplanada Farm, in Goianésia / Goiás, from June / 2015 to July / 2016, in medium texture soil with conventional tillage and transplanting of seedlings in irrigated areas of 100 ha (central pivot). In addition, plant height, stem diameter, leaf temperature, yield and juice quality were monitored. The water status of the soil and the plant revealed that there was no water deficit during the cycle of 398 days. The results also showed that for the estimation of sugarcane evapotranspiration the SAFER method overestimated the ETBHS in 22.89%. Despite of the ETa estimated by the SAFER method to present a significant correlation with the water balance method (R2 = 0.7778), other studies must be conducted before being recommended for estimation of sugarcane ETa in the region.